A Hypermedia-Supported program and its effect on developing historical reasoning skills among first year secondary school students - kholoud ibrahem; Samia Fayed (International Journal of Instructional Technology and Educational Studies)
This study investigated the effect of a hypermedia-supported program on developing historical reasoning skills among first-year secondary school students in Egypt. A quasi-experimental design with an experimental group (n=30) receiving instruction through the hypermedia program and a control group (n=30) receiving traditional instruction was employed. Historical reasoning skills were assessed across six components: asking historical questions, using sources, contextualizing, using evidence and arguments, using historical concepts, and using meta-historical concepts. Results from independent samples t-tests revealed the experimental group significantly outperformed the control group on all components and overall historical reasoning skills (p<.01). The findings suggest integrating hypermedia, which combines multimedia elements with interactive and non-linear navigation, can enhance secondary students' ability to critically analyze historical sources, contextualize events, construct evidence-based arguments, and apply key historical concepts. This supports leveraging technology-enabled, student-centered approaches aligned with multimedia learning theory and constructivist pedagogies to foster historical reasoning competencies vital for developing nuanced understandings of the past. Implications for educational technology implementation in history curricula are discussed.